The Influence Of Trusting Beliefs And Intention To Continue Purchasing on E-Commerce Shopee - Prastiwi, Tiara Indra; Ellitan, Lena (Journal of Entrepreneurship & Business, 2025)
Purpose: This research aims to determine the influence of trusting beliefs and intentions on people to continue making purchases on Shopee e-commerce. As time progresses, there are more and more other digital platforms that can also make it easier for people to make purchases. However, this research specifically discusses whether the e-commerce platform can be trusted by old and new consumers through 5 variables, namely Competence, Integrity, Virtue, Purchase Intention, Purchase and Post Purchase. Method: The sampling technique for this research is non-probability sampling with purposive sampling technique. The sample used in this research was 267 respondents with the criteria of being aged 17 years and over and who had purchased Scarlett Whitening products on Shopee e-commerce in the last 3 months. Result: The findings of this study indicate that two hypotheses were not supported: the effect of integrity on purchase intentions, and the effect of integrity on purchases and post-purchase behavior through purchase intentions. In contrast, five hypotheses were supported. These include the effect of competence on purchase intentions, the effect of benevolence on purchase intentions, the effect of purchase intentions on purchases and post-purchase behavior, the effect of competence on purchases and post-purchase behavior through purchase intentions, and the effect of benevolence on purchases and post-purchase behavior through purchase intentions. Based on these findings, it is recommended that official Scarlett Whitening stores operating on the Shopee platform improve their consistency in serving both new and existing customers.